1984
DOI: 10.1159/000194668
|View full text |Cite
|
Sign up to set email alerts
|

Elektromyographische Bestimmung der Ermüdbarkeit von Atem- und Beinmuskeln vor und nach aortokoronarer Bypass-Operation

Abstract: To study the effect of postoperative confinement to bed on respiratory muscle fatigue, 31 male subjects (age, 34–66 years) undergoing coronary artery revascularization were examined. Fatigue of both respiratory muscles (musculi intercostales externi) and leg muscles (musculus gastrocnemius) was determined by electromyography prior to and 7 and 12 days after operation. Additionally, oscillatory resistance to breathing and phase angle were measured. Pre- and postoperative routine lung function tests were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The postoperative ventilation problems could be due to either zones of atelectasis (found in Ͼ 30% of patients after the surgery) [5], pleural changes such as effusion or thickening (found in Ͼ 40% of the patients) [11], abnormal rib cage motion secondary to the trauma of surgery [12], and respiratory muscle weakness, as was found in most of the patients following CABG [4]. Respiratory muscles may be injured directly or indirectly during CABG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The postoperative ventilation problems could be due to either zones of atelectasis (found in Ͼ 30% of patients after the surgery) [5], pleural changes such as effusion or thickening (found in Ͼ 40% of the patients) [11], abnormal rib cage motion secondary to the trauma of surgery [12], and respiratory muscle weakness, as was found in most of the patients following CABG [4]. Respiratory muscles may be injured directly or indirectly during CABG.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many studies showed that there is decreased postoperative alveolar ventilation, gas exchange [5], and lung function [6,7]. Few studies have investigated the respiratory muscle performance after CABG, but they have shown a decrease in the respiratory muscle strength and unior bilateral phrenic nerve paralysis [4]. It is reasonable to assume that the respiratory muscle weakness is associated with direct or indirect injury to the respiratory muscles during surgery, which may lead to respiratory muscle dysfunction and respiratory failure.…”
mentioning
confidence: 99%
See 1 more Smart Citation